2021
DOI: 10.2147/jir.s315981
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Clinical Significance of ACE2 and Its Age-Related Expression

Abstract: Background ACE2 plays a particular role in the changes in multiple organ functions. However, whether ACE2 expression differs at different ages and whether it plays a role in infection-related organ dysfunction remains unclear. Methods Female and male C57BL/6 mice in four different age groups were included in this study. Immunohistochemical and Western blot analyses were performed to evaluate ACE2 expression characteristics in lung tissues. At the same time, we detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This finding could be explained by age-related changes in the immune system, resulting in a decreased immune response to infections in the elderly population. In contrast, a more robust immune response to infections is preserved in younger patients and it leads to increase the risk of SAT following COVID-19 [ 31 ]. Another plausible mechanism for the higher incidence of SAT in young age could be attributed to the higher expression of ACE2 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be explained by age-related changes in the immune system, resulting in a decreased immune response to infections in the elderly population. In contrast, a more robust immune response to infections is preserved in younger patients and it leads to increase the risk of SAT following COVID-19 [ 31 ]. Another plausible mechanism for the higher incidence of SAT in young age could be attributed to the higher expression of ACE2 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, SARS-CoV-2 infection may lead to a decrease in the ACE2 protein levels, which may increase the expression of pro-inflammatory mediators, leading to increased severity and higher mortality of COVID-19 [ 22 , 23 , 24 , 25 ]. This is of particular importance in older patients, as ACE2 levels decline with age, making them more vulnerable to the immunologic consequences associated with the ACE2 level reduction induced by SARS-CoV-2 [ 26 ]. Moreover, anatomical changes in the lungs and the potential for atrophy of the respiratory muscles can be associated with changes in respiratory function, making older individuals more vulnerable to complications of COVID-19 due to a reduction in the respiratory reserve and decreased defense barriers.…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 receptor expression has been described to both increase (Baker et al, 2021;Wark et al, 2021) and decrease (Chen et al, 2020;J. ;Gu et al, 2021;Xudong et al, 2006;Yoon et al, 2016) with age in humans and rodents. However, Berni Canani et al (2021) observed no significant differences in ACE2 expression between children <10 years old and adults 20-80 years old, detected this same trend when comparing expression across multiple tissues in adults above or below 49 years of age.…”
Section: Agementioning
confidence: 99%